2020
DOI: 10.1177/0009922820941629
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Determinants of Pediatric Antibiotic Use

Abstract: Introduction. Evidence suggests that early-life antibiotic use can alter gut microbiome, predisposing children to obesity. The obesity epidemic has a disproportionate effect on individuals from lower socioeconomic status (SES). Thus, this study aims to explore the link between SES and antibiotic use. Design. We performed a retrospective cohort study of all babies born at and receiving 2 or more outpatient visits at a large, suburban health system in Illinois (United States) between 2007 and 2017. We collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(46 reference statements)
0
6
1
Order By: Relevance
“…However, even in newborns with the lowest risk of sepsis, (e.g., cesarean delivery, without labor or membrane rupture before delivery, and no antepartum concern for intra-amniotic infection or non-reassuring fetal status), a large retrospective cohort study found that 80% of term and preterm infants were administered antibiotics at the time of birth hospitalization [24]. Surprisingly, we found higher rates of AU among Black newborns compared to other races in contrast to other pediatric studies [25,26]. This could probably be due to clinical severity, prescribers' bias, parental expectations and presumed higher risk of early onset sepsis in African-American population [8,9].…”
Section: Accepted Manuscriptcontrasting
confidence: 75%
See 1 more Smart Citation
“…However, even in newborns with the lowest risk of sepsis, (e.g., cesarean delivery, without labor or membrane rupture before delivery, and no antepartum concern for intra-amniotic infection or non-reassuring fetal status), a large retrospective cohort study found that 80% of term and preterm infants were administered antibiotics at the time of birth hospitalization [24]. Surprisingly, we found higher rates of AU among Black newborns compared to other races in contrast to other pediatric studies [25,26]. This could probably be due to clinical severity, prescribers' bias, parental expectations and presumed higher risk of early onset sepsis in African-American population [8,9].…”
Section: Accepted Manuscriptcontrasting
confidence: 75%
“…24 Surprisingly, we found higher rates of AU among Black newborns compared with other races in contrast to other pediatric studies. 25,26 This could probably be due to clinical severity, prescribers' bias, parental expectations, and presumed higher risk of early-onset sepsis in African American population. 8,9 Higher AU in deliveries with chorioamnionitis is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Population age and sex, the average income per household, the ratio of upper secondary graduates going to further education and the average age of physicians were obtained from Statistic Bureau, Ministry of Internal Affairs and Communications [22]. The physician's age was included in the variables because some studies showed physicians' experience is related with antibiotic prescriptions [13,17]. The number of clinics, the number of hospitals, the rate of hospitals with > 500 beds and the number of healthcare facilities with additional reimbursement for infection prevention 1 and 2 were obtained from regional bureaus of Health and Welfare (e.g., Kanto-Shinetsu) [24,25].…”
Section: Variablesmentioning
confidence: 99%
“…While geographical variabilities of AMU within a country were reported in some studies, the evidence regarding the factors affecting the geographical variation of AMU is relatively scarce [8, 9,10,11,12]. In general, physician-level factors (e.g., physician's experiences) and patient-level factors (e.g., patient age, sex and socioeconomic status) have been reported to impact physician's behavior of antimicrobial prescription [13,14,15,16,17,18]. The investigation of these factors to evaluate their potential impact on geographical variability using nationwide data may contribute to the identi cation of potential measures to reduce AMU and the promotion of appropriate AMU in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In many ways, microbiome science has served to illuminate the unseen or otherwise ignored links between health at personal, public, and planetary scales—in tangible and measurable ways. For example, in addition to over‐prescription of antibiotics, 59 many other factors such as air pollution, 60 environmental toxins, 61 psychological stress, 62 , 63 ultra‐processed food 64 and dietary advanced glycation end‐products (AGEs), 65 emulsifiers, 66 phthalates 67 ), sleep disruption, 68 tobacco use, 69 sedentary behavior, 70 and excess alcohol consumption, 71 have been shown to impact the microbiome. Again.…”
Section: The Microbiome As a Mediator And A Measure Of Unhealthy Systemsmentioning
confidence: 99%